Proposed children's land at Bukit Gasing, Petaling Jaya, Selangor darul Ehsan - Farekha Resat
The proposed children's land is focusing on the creation of an environment that promotes environmental awareness among school children. Education is the most effective method used to make people aware of the environmental issue and when it involves school children, a suitable environment is needed. The kind of environment that is suitable must be safe, supports their developmental needs, and by providing facilities children can enjoy and learn about the environment in a comfortable way. Environmental education is being taught at schools and by bringing it out to the real outdoor, children can understand more by experimenting, and experiencing the real environment. The main goal for the Proposed Children's Land is to create an environment where school children can learn and have fun in a natural surrounding, besides promoting environmental awareness among them. The design of the Children's Land is based on nature themes, as the chosen site is a secondary forest. The nature surrounding that is suitable for nature activities need only minimal development in order not to disturb the habitat. By creating such environment more children will realise the importance of the nature environment, as they are the builders of the future.